The Importance of Digital Technologies in Improving the Efficiency of Manufacturing Enterprises (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In the article, the authors conducted research on the digitization of the activities of the enterprises in order to increase the efficiency of the activities of the production enterprises and developed suggestions and recommendations. They also gave conclusions on the systematic digitization of production enterprises.